Modern aspects of strategies for developing single-phase broadly tunable white light-emitting phosphors. Issue 38 (20th September 2021) - Khan, Sayed Ali; Khan, Noor Zamin; Sohail, Muhammad; Ahmed, Jahangeer; Alhokbany, Norah; Alshehri, Saad M.; Xu, Xin; Zhu, Jinfeng; Agathopoulos, Simeon
Abstract : The latest developments of single-phase white-light-emitting Ba9 Lu2 Si6 O24 (BLSO) silicate phosphors are presented. The emerging approaches to crystal-site engineering and the energy transfer mechanisms are discussed at great length. Abstract : In phosphors intended for the applications of white light-emitting diodes (white-LEDs), their ability to achieve controlled-photoluminescence-tuning is an important feature, which is directly linked to their optimization and modification. More specifically, the development of luminescent materials with broadly and continuously tunable photoluminescence is still a challenge for the generation of highly efficient warm white-light with appropriate correlated color temperature (CCT), a high color-rendering-index (CRI), and excellent thermal stability. This review presents the latest developments of single-phase white-light-emitting Ba9 Lu2 Si6 O24 (BLSO) silicate phosphors. The emerging approaches to crystal-site engineering and the energy transfer mechanisms are discussed at great length. The BLSO phosphor host lattice, having rich and distinguishing crystallographic sites, provides various surrounding environments to the doped rare-earth (RE) ions, and it also allows for the engineering of the local atmosphere of the doped ions. Substitution with more than one activator, as a co-dopant ion, in the BLSO phosphor host may enable tuning of the photoluminescence spectrum to the desired spectral region. The ultimate goal of this review is to aid research aimed at discovering new approaches to the aforementioned objectives, following strategies associated with the occupation of multiple crystallographic sites with activators, in accordance with a thorough understanding of the function of the energy-transfer phenomenon, whereby various dopants can achieve efficient tunability.